Preface - Danko Markovinović; Vlado Cetl; Milan Kljajin (Tehnički Glasnik)
This Preface clarifies the reason for issuing the Special Issue and its content. Twelve published articles were orally presented during the COBGI24 workshop (https://figcom3-ws-croatia2024.hgd1952.hr/), which focused on the challenges and opportunities in BIM and GIS integration. The event took place in Varazdin at University North (Croatia) from June 18 to June 21, 2024.